2021
DOI: 10.1111/jcmm.16361
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of GSTP1 in the aqueous humour of patients with primary open‐angle glaucoma

Abstract: Primary open‐angle glaucoma (POAG) is characterized by irreversible neurodegeneration accompanied by visual field defects and high intraocular pressure. Currently, an effective treatment is not available to prevent the progression of POAG, other than treatments to decrease the high intraocular pressure. We performed proteomic analysis of aqueous humour (AH) samples from patients with POAG combined with cataract and patients with cataract to obtain a better understanding of the pathogenesis of POAG and explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…COTL1 overexpression showed disturbed neuronal morphology and exhibited AD-like neuropathology [ 82 , 83 ]. In a study with POAG patients, COTL1 was up-regulated in aqueous humor [ 84 ]. Therefore, the low abundance of COTL1 suggested continued polymerization and stabilization of the actin cytoskeleton, which, together with MT cytoskeleton stabilization, may be part of a neuroprotective mechanism, as shown in previous studies [ 26 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…COTL1 overexpression showed disturbed neuronal morphology and exhibited AD-like neuropathology [ 82 , 83 ]. In a study with POAG patients, COTL1 was up-regulated in aqueous humor [ 84 ]. Therefore, the low abundance of COTL1 suggested continued polymerization and stabilization of the actin cytoskeleton, which, together with MT cytoskeleton stabilization, may be part of a neuroprotective mechanism, as shown in previous studies [ 26 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method of proteolysis was based on sodium dodecyl sulphate polyacrylamide gel electrophoresis as performed previously 26 . The SDS‐PAGE was performed with 5 μg of protein per sample; the gel was stained and then destained until the background was clear.…”
Section: Methodsmentioning
confidence: 99%
“…20 The application of this technology to different diseases has improved our understanding of disease mechanisms [21][22][23] and highlighted new disease biomarkers and therapeutic methods. [24][25][26] In this study, we initially hypothesized that angle closure is related to AH change in primary angle-closure glaucoma (PACG) and some proteins in AH could reflect the anterior chamber angle before neuropathy. The aim of this study was to analyse the characteristics of differentially expressed proteins (DEPs) based on the AH proteomes of APAC patients and to discover valuable information for treatment in the early stage of PACG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of liquid biopsies for diabetic retinopathies and other vitreoretinal diseases was also noted for precision medicine [13,14]. Recent proteomics studies of human AH revealed many proteins in patients with intraocular disease [13,[15][16][17][18][19]. Pollreisz et al [20] first performed isobaric tags for relative and absolute quantitation (iTRAQ) 4-plex quantitative protein analysis of the aqueous and vitreous fluids from human eyes with iERM.…”
Section: Introductionmentioning
confidence: 99%